1997
DOI: 10.1073/pnas.94.22.11786
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions among the Aux/IAA proteins

Abstract: The plant hormone indoleacetic acid (IAA) transcriptionally activates early genes in plants. The Aux͞IAA family of early genes encodes proteins that are short-lived and nuclear-localized. They also contain a putative prokaryotic ␤␣␣ DNA binding motif whose formation requires protein dimerization. Here, we show that the pea PS-IAA4 and Arabidopsis IAA1 and IAA2 proteins perform homo-and heterotypic interactions in yeast using the two-hybrid system. Gel-filtration chromatography and chemical cross-linking experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
428
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 493 publications
(437 citation statements)
references
References 41 publications
7
428
0
2
Order By: Relevance
“…cently, it has been demonstrated that Aux/IAA proteins homo-and heterodimerize in vitro and in vivo [12]. Moreover, Aux/IAA proteins interact with members of the A R F protein family of transcription factors that contain C-terminal, Aux/ IAA-like domains III and IV [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…cently, it has been demonstrated that Aux/IAA proteins homo-and heterodimerize in vitro and in vivo [12]. Moreover, Aux/IAA proteins interact with members of the A R F protein family of transcription factors that contain C-terminal, Aux/ IAA-like domains III and IV [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Aux/IAA proteins interact with members of the A R F protein family of transcription factors that contain C-terminal, Aux/ IAA-like domains III and IV [9,12]. Using a yeast two-hybrid system, deletion analysis of the PS-IAA4 protein from pea revealed that the C-terminus of PS-IAA4, containing domains III and IV, is necessary and sufficient for dimerization [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations